Agenda Setting in Emergent R&D Policy Subsystems: Examining Discourse Effects of the 21st Century Nanotechnology Research and Development Act. Issue 5 (7th October 2013) - Anderson, Derrick; Slade, Catherine P.
Abstract The literature on government responsiveness to societal issues is extensive but provides a mixed assessment of effectiveness. We examine this issue in the case of policy addressing effective and safe management of research and development in the emerging field of nanotechnology. Specifically, we examine the agenda setting effects of the 21st Century Nanotechnology Research and Development Act (the Act), a piece of legislation designed to be implemented by a network of actors in the nanotechnology research and development policy subsystem. We adopt a public values lens in our examination of discourse related to societal concerns. Policy documents from Congress, an agency, and federal funding recipients are examined. Findings suggest a narrowing of public values discourse around more specific societal concerns in the documents crafted after the Act was passed.